The current state of Italian language and culture teaching in higher education in China - Gu, Shuangshuang (Frontiers in Education, 2025)
In the growing context of economic globalization, trade and exchanges between countries around the world are more and more frequent. This brings about an increasing demands of experts in foreign languages. It has been already 71 years since the University of International Business and Economics (UIBE) in Beijing launched the first Italian language program in 1954. Currently, there are 24 universities and institutes across the country (including Hong Kong and Macao) offer the academic degree related to Italian language and culture. Furthermore, many other universities and higher education institutions provide Italian language courses. This paper briefly reviews the history of teaching Italian language and culture in China. The aim of this study is to provide a comprehensive overview regarding the current state of teaching Italian language and culture within Chinese higher education system. This paper also covers the relevant teachers’ educational background, their academic titles and the use of teaching material, etc. In particular, this study sheds some light on the state of teaching the aforementioned subjects in Chinese institutions (universities, institutes, vocational and technical institutes) that provide Italian language and culture as elective, compulsory or minor courses, and the teaching situation to graduate students, which was not thoroughly explored in previous studies. Furthermore, this paper shows the various types of course program, the number of students enrolled and some peculiar difficulties of providing these kinds of courses to Chinese learners.